The marketplace of print : pamphlets and the public sphere in early modern England - Halasz, Alexandra (New York, NY, USA : Cambridge University Press, 1997)
Early modern pamphlets serve as an important vehicle for examining print culture, particularly the historical entanglement between the technology of print and a developing capitalism. Attention to the controversies surrounding their circulation reveals that pamphlets became a focus for anxieties about print culture in general. Alexandra Halasz combines close readings of pamphlets by Robert Greene, Thomas Nashe, Gabriel Harvey, Thomas Deloney and John Taylor, among others, with a discussion of the history and deployment of print technology and its specifically English organization as a monopoly. Taking account of the theoretical and historical issues surrounding textual property, authorship and publicity, The Marketplace of Print, first published in 1997, is both a work of historical recovery and a reflection on the ongoing problems of the relationship between the marketplace and the public sphere.
1. Print matters -- 2. Figuring the marketplace of print -- 3. The patrimony of learning -- 4. Artisanal dispossession -- 5. The public sphere and the marketplace.
Includes bibliographical references (pages 225-236) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Pamphlets -- Publishing -- England -- History -- 16th century; Pamphlets -- Publishing -- England -- History -- 17th century; Printing -- Social aspects -- England -- History -- 16th century; Printing -- Social aspects -- England -- History -- 17th century; Public opinion -- England -- History -- 16th century; Public opinion -- England -- History -- 17th century; Authorship -- History -- 16th century; Authorship -- History -- 17th century; Opinion publique -- Angleterre -- Histoire -- 16e siècle.; Opinion publique -- Angleterre -- Histoire -- 17e siècle.; Art d'écrire -- Histoire -- 16e siècle.; Art d'écrire -- Histoire -- 17e siècle.; Pamphlets -- Édition -- Angleterre -- Histoire -- 16e siècle.; Pamphlets -- Édition -- Angleterre -- Histoire -- 17e siècle.; LANGUAGE ARTS & DISCIPLINES -- Publishing; Authorship; Pamphlets -- Publishing; Printing -- Social aspects; Public opinion; England; Pamphlet; Flugblatt; Buchmarkt; England; Englisch; Engels; Pamfletten; Maatschappij; Markt; Édition -- Grande-Bretagne -- 1485-1603 (Tudors); Industrie du livre -- Grande-Bretagne -- 1485-1603 (Tudors); Pamphlets -- Grande-Bretagne -- 1485-1603 (Tudors); Imprimerie -- Grande-Bretagne -- Histoire -- 16e siècle.; Pamphlets -- Édition -- Grande Bretagne -- 17e siècle.; Imprimerie -- Aspect social -- Grande Bretagne -- 17e siècle.; Geschichte 1580-1640.; Englisch; 1500-1699; Electronic books; History